Questions in Aesthetic Education (RLE Edu K). - Redfern, H. B. (Routledge library editions. Education., 2012)
The Question of what 'aesthetic education' is, or might be, is often a source of incomprehension. This book opens up discussion of a complex, difficult, but highly important topic, and offers an introductory survey of the whole area. In examining the relationship of the concept of the aesthetic to that of art, it challenges the persistent linking by many educationists of 'aesthetic' with 'creative' and the consequent neglect of critical reflection and appreciation.